Midline epidermal inclusion cyst of neck in children: a diagnostic dilemma: case report and review of literature - Bachala, Keerthana; Sinha, Amit Kumar; Dudhani, Shreyas; Jana, Sourav; Vaze, Prajakta (International Journal of Contemporary Pediatrics, 2025)
Painless midline neck swellings have been a challenging confrontation for any surgeon, mostly due to numerous diagnostic possibilities at this location. Common ones include thyroglossal cyst, epidermoid cyst, dermoid cyst, enlarged lymph nodes, vascular anomaly etc. Due to a different treatment modality for each entity, proper diagnosis is necessary. We are presenting two cases of midline epidermal inclusion cyst having unique clinical and radiological features, creating a diagnostic query.